Relationship between lipid profiles with carotid intima–media thickness in children with type I diabetes mellitus - Rubiana Sukardi; Bambang Madiyono; Sudigdo Sastroasmoro; Jose RL Batubara (Indonesian Pediatric Society, 2008)
Background The major cause of morbidity and mortality inpatients with type I diabetes mellitus is premature and extensiveartherosclerosis. Carotid intima-media thickness (IMT) isassociated with cardivascular risk factors and has been used as amarker of early artherosclerosis process.Objective To determine IMT of carotid artery and its relationshipwith duration of diabetes, lipid profiles, and mean HbA 1 level.Methods A cross-sectional study was conducted on patientswith type 1 DM at the Department of Child Health CiptoMangunkusumo Hospital. Ultrasound B-mode imaging wasperformed to measure the IMT. Age-matched non-diabteticsubjects served as controls. Statistical significant was assumedat P<O.S.Results The mean IMT values of type I DM patients aged < 12years, 12-18 years, 18+ years were 0.44 (SD 0.03) mm; 0.46(SD 0.01) mm; 0.51 (SD 0.01) mm, respectively, which weresignificantly greater than those of age-matched non-diabeticsubjects which were 0.39 (SD 0.01), 0.41 (SD 0.01) mm, 0.46(SD 0.01) mm, respectively. Patients with type I DM had ahigher apolipoprotein-Band HDL cholesterol levels than in non-diabetic subjects. Multiple regression analysis showed that therewas no relationship between total cholesterol, cholesterol LDL,chronic hyperglycemia (HbA 1) and IMT. However, IMT in typeI diabetes was linearly related with duration of diabetes .Conclusion Type I DM patients have greater IMT and highermean apolipoprotein B. There is a strong correlation betweenIMT and duration of diabetes.